O ensino de língua portuguesa no Brasil: discursos materializados em documentos oficiais e atualizados pelo PCN e pela BNCC - Fancio, Adriana Cicera Amaral (2019)
This research has as general objective to analyze the most recent official discursive construction about the Portuguese Language (hereinafter LP) as a teaching object based on the discursive and comparative analysis of the two Brazilian prescriptive documents, namely the National Curricular Parameters (BRAZIL, 1998) and the National Curricular Common Base (BRAZIL, 2017). It is characterized as a qualitative investigation, of theoretical and analytical nature, with procedures of documentary analysis and bibliographic revision, anchored in the perspective of Discourse Analysis (AD) and articulation with the History of Linguistic Ideas (HIL) in Brazil. It is therefore embedded in the previous theoretical reflections on the institutionalization of language as official and national in the country (GUIMARÃES, 2005a), permeated by linguistic policies and relations of force (ORLANDI, 2007a). From the bibliographical analysis, gestures of interpretation of the materiality of the archive (PÊCHEUX, 1982) were performed, in order to provide a better understanding of the silences and meanings that are affected by the conditions of production ((PÊCHEUX, 1981; COURTINE, 1982; ORLANDI, 2015) and the interactions among the subject, the history and the ideological positions that contribute to the construction of the Brazilian linguistic identity (ORLANDI, 2007a, 2015). The Discourse Analysis materialized in the archive about LP as a teaching object in the school showed that the BNCC (2017) updates some discourses enunciated in the PCN (1998) and presents others, such as the organization of teaching in language practices and fields of action. In addition, the analyses showed that LP, in a way, is still seen as the mother tongue of Brazilians producing the coincidence effect (PFEIFFER; SILVA, 2014) in relation to the imaginary language (ORLANDI, 1990). We also recognize the effort, in a certain way, highlighted in the discourse materialized in the recent BNCC (2017), to recognize the linguistic varieties when proposing discussions about the diversity of languages spoken in Brazil, to avoid linguistic prejudice. Finally, another official document presents to society the discourse of improvement of the educational system in Brazil. The complexity of Brazilian education, in short, requires much investment, reorganization of the public policies and language policies.